2016
DOI: 10.1371/journal.pone.0148707
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Network of Naming: A Lesson from Primary Progressive Aphasia

Abstract: ObjectiveWord finding depends on the processing of semantic and lexical information, and it involves an intermediate level for mapping semantic-to-lexical information which also subserves lexical-to-semantic mapping during word comprehension. However, the brain regions implementing these components are still controversial and have not been clarified via a comprehensive lesion model encompassing the whole range of language-related cortices. Primary progressive aphasia (PPA), for which anomia is thought to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 61 publications
(96 reference statements)
6
45
0
4
Order By: Relevance
“…Tau uptake bilaterally in the frontal and temporal lobe was associated with deficits in sentence repetition, as well as in the left parietal region, likely reflecting disruption of the language network [48]. There was also a trend for tau uptake in both temporal lobes to be associated with poorer naming, concordant with the role of the temporal lobes in anomia and semantic processing [49]. Tau uptake bilaterally in the occipital lobe was related to severity of both simultanagnosia and visuoperceptual function, features which have previously been associated with dysfunction in the occipital lobe [4, 17, 43, 5052].…”
Section: Resultsmentioning
confidence: 99%
“…Tau uptake bilaterally in the frontal and temporal lobe was associated with deficits in sentence repetition, as well as in the left parietal region, likely reflecting disruption of the language network [48]. There was also a trend for tau uptake in both temporal lobes to be associated with poorer naming, concordant with the role of the temporal lobes in anomia and semantic processing [49]. Tau uptake bilaterally in the occipital lobe was related to severity of both simultanagnosia and visuoperceptual function, features which have previously been associated with dysfunction in the occipital lobe [4, 17, 43, 5052].…”
Section: Resultsmentioning
confidence: 99%
“…Abel et al provided neurophysiological evidence that the left and right anterior temporal lobe showed robust beta-band during visual naming of famous people and tools {52}. In studies investigating the temporal lobe in language processing in PPA, Wilson et al demonstrated that its role in sentence processing is likely to relate to higher-level processes such as combinatorial semantic processing {53}, while Migliaccio and colleagues demonstrated its role in binding of lexical and semantic information in bidirectional manner {54}. As Chinese is a logographical language, where semantic data is tagged to each individual character, we speculate that this region also serves as a center of convergence of lexical semantics of the language, particularly in logographical languages.…”
Section: Discussionmentioning
confidence: 99%
“…Such evolutions towards distinct jargonaphasia phenotypes are in line with the distinct language deficits in the 2 PPA variants. Lv-PPA is characterized by progressive erosion of the phonological lexicon in posterior temporal regions [23,36], whereas semantic PPA leads to the breakdown of semantic representations in anterior temporal regions [23]. Lv-PPA therefore leads to structural distortions of the output lexicon with instable and blurred lexical representations, which is the causative factor of phonemic or syllabic inversions/substitutions/insertions.…”
Section: Discussionmentioning
confidence: 99%